ENHANCING THE STUDENTS READING COMPREHENSION MASTERY, MOTIVATION AND INTEREST THROUGH DIGITAL STORYTELLING - Diyah Dwi Agustina (Universitas Nahdlatul Ulama Lampung, 2016)
This research is Classroom Action Research. The participant of the research is done in the class VIIA of SMP 1 Raman Utara, East Lampung. Meanwhile, this research employs the triangulation method (observation, interview, and test) to collect the data. After the data are gathered, they are analyzed and interpreted by using data reduction, categorization and synthesis. The findings were formulated as follow: (1) the implementation used more varieties media in presenting the materials using digital storytelling such as the combination of text picture, animation, video and sounds. Most of the students become more active in learning process; (2) the improvement of students’ reading comprehension achievement could be seen from the test, the mean score improved from 57 in cycle 1 become 71 in cycle 2. Then, in cycle 3 the score is 78 or all of the students pass the minimum passing grade; (3) there is improvement in the students learning motivation and interest. It could be seen from` the observation result, questionnaire and interview. Most of the students were less interested and low motivation during teaching and learning process before the implementation